First-line treatment with durvalumab plus chemotherapy versus chemotherapy alone for metastatic non-small-cell lung cancer in the USA: a cost-effectiveness analysis - Ling Fang; Zhiwei Zheng; Hongfu Cai (BMJ Open, 2023)
Objective The objective of this study was to evaluate the cost-effectiveness of durvalumab in combination with chemotherapy compared with chemotherapy alone as first-line therapy for metastatic non-small-cell lung cancer (NSCLC) from the perspective of the US payer.Methods Based on the POSEIDON clinical trial, a partition survival model was developed to compare the cost-effectiveness of durvalumab in combination with chemotherapy versus chemotherapy alone for the first-line treatment of metastatic NSCLC. The model’s primary outcomes were costs, life years (LYs), quality-adjusted LYs (QALYs) and the incremental cost-effectiveness ratio (ICER). The analysis only considered direct medical costs, and health utility value was determined using published literature. The robustness of the model was tested by probabilistic sensitivity analyses.Results The combination therapy of durvalumab and chemotherapy improved survival by 0.713 QALYs at an incremental cost of $64 104.638 compared with chemotherapy alone, resulting in an ICER of $89 908.328 per QALY gained from the US payer perspective. The combination therapy had a 92.3% probability of being cost-effective at a willingness-to-pay threshold of $150 000 per QALY based on incremental net health benefits. Sensitivity analyses confirmed the model’s consistency, and none of the parameters significantly influenced the findings.Conclusion Durvalumab in combination with chemotherapy represents a more cost-effective strategy for first-line therapy in patients with metastatic NSCLC in the USA compared with chemotherapy alone.